Metode Simple Additive Weighting (SAW) dalam Pemilihan Media Pembelajaran Bahasa Korea - Ramanda, Kresna; Sundari, Wiwin; Rusman, Arief; Sikumbang, Erma Delima; Sukmana, Sulaeman Hadi; Azizah, Qudsiah Nur (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Almost all Asian countries experience the Korean Wave phenomenon. Asian countries such as Japan, China, Taiwan, Hong Kong, Thailand, Philippines, Singapore, Malaysia, Indonesia and others. With such a phenomenon, it can be observed that if someone likes something from abroad, most people are interested in learning the language. However, it is still difficult for them to find Korean language learning solutions. And one solution is to use appropriate learning media to support learning. The simple additive weight (SAW) method, also known as the weight sum method, will be applied in this study. The SAW method can select the best alternative from several available alternatives because it is ranked after determining the weight of each feature. The results showed that alternative or mobile learning at A2 is the best learning media for Korean and the simple additive weight (SAW) method can determine the best choice of Korean language learning environment. Keywords: Simple Additive Weighting, learning media, Korean language